SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN LOKASI USAHA WARALABA MENGGUNAKAN METODE BAYES - Diana, Diana (Universitas Bina Darma, 2017)
The aim of this research is to develop a decision support system to determine the location of the franchise for determining strategic business location has a big share a role in determining the success of a company.Step-solving is SDLC approach includes the following phases: 1) planning, 2) analysis, 3) design, 4) implementation and 5) maintenance. The method applied is the method of Bayes. Decision-making with Bayesian methods require information about the probability of each alternative on issues faced to generate the expected value as a basis for decision making. This research resulted in a decision support system to determine the location of the franchise by applying Bayesian methods. In the testing phase, based on the results of five trials with a variety of data obtained by the fact that the order of business location recommendations provided by the system is consistent. Keywords: decision support system, bayesian methods, business location